Projected shrinking of tropical vegetation biomass potential with future hydroclimatic shifts - Félicien Meunier; Marijn Bauters; Pascal Boeckx; Philippe Ciais; Steven J De Hertog; Wim Thiery; Yitong Yao; Hans Verbeeck (Environmental Research Letters, 2025)
Global change threatens the carbon stocks stored in tropical ecosystems. However, considerable uncertainty remains regarding the estimates of these future carbon losses. Here, we analysed Earth system model (ESM) simulations to assess future changes in tropical vegetation biomass potential due to shifts in the hydrological cycle. We found that tropical ecosystems could experience substantial decreases in vegetation biomass potential, particularly under high-emission scenarios, due to decreasing precipitation, increasing evaporation demand, and higher rainfall seasonality. These declines are principally driven by the transition of Amazon rainforests towards drier ecosystems. However, the difference in tropical vegetation biomass potential between most extreme ESMs reached 73 Pg C at the end of this century for the shared socio-economic pathway (SSP) 2–4.5 and 147 Pg C for SSP5-8.5. Weighting models based on their ability to reproduce the current hydroclimate in the tropics resulted in a reduction of vegetation biomass potential by 2100 in SSP2-4.5 of 12 Pg C (8–16 Pg C) compared with a simple average of all ESMs which gave 20 Pg C (17–24 Pg C). Our findings underscore the urgent need to reduce not only direct anthropogenic disturbances but also the rate of global greenhouse gas emissions to preserve the vegetation biomass potential of tropical ecosystems.